Atomic and molecular absorption in redshifted radio sources - Curran, SJ; Whiting, MT; Allison, JR; Tanna, A; Sadler, EM; Athreya, R (Oxford University Press, 2017)
We report on a survey for associated H I 21-cm and OH 18-cm absorption with the Giant Metrewave Radio Telescope at redshifts z ≈ 0.2–0.4. Although the low-redshift selection ensures that our targets are below the critical ultraviolet luminosity (LUV ∼ 1023 W Hz−1), which is hypothesized to ionize all of the neutral gas in the host galaxy, we do not obtain any detection in the six sources searched. Analysing these in context of the previous surveys, in addition to the anticorrelation with the ultraviolet luminosity (ionizing photon rate), we find a correlation between the strength of the absorption and the blue–near-infrared colour, as well as the radio-band turnover frequency. We believe that these are due to the photoionization of the neutral gas, an obscured sightline being more conducive to the presence of cold gas and the compact radio emission being better intercepted by the absorbing gas, maximizing the flux coverage, respectively. Regarding the photoionization, the compilation of the previous surveys increases the significance of the critical ionizing photon rate, above which all of the gas in the host galaxy is hypothesized to be ionized (⁠QHi≈3×1056 s−1), to >5σ. This reaffirms that this is an ubiquitous effect, which has profound implications for the detection of neutral gas in these objects with the Square Kilometre Array.